Purposive Communication is Not Enough: Exploring English Language Learning from the perspectives of English majors in a Philippine Higher Education Institution - Rafael Michael Paz (Pascasarjana Universitas Negeri Makassar, 2021)
The structural changes brought by the K to 12 basic education program significantly impact not only ELT and ELL in basic education, but ELT and ELL in higher education as well. English language courses in the higher education general education domain were phased out, or for the majority of HEIs in the Philippines, reduced to a course called Purposive Communication. Using data from students who had taken Purposive Communication in their year 1 in the university, this paper argues that Purposive Communication is not enough to reinforce all the English language skills expected for higher education students to perform during and after their time in the university. This paper invokes policy implementers to consider the inclusion of additional English-language courses in higher education to provide avenues for students to practice their communication skills in English and address the country’s declining proficiency in using the English language.